Determination of multi element levels in leaves and herbal teas from Turkey by ICP-OES - E. Altıntıg; H. Altundag; M. Tuzen (Bulletin of the Chemical Society of Ethiopia, 2014)
We have determined the amount of some heavy metals (Al, Ba, Cr, Cu, Fe, Mn, Ni, Sr and Zn) contained in 18 herbal tea samples that had been bought from local markets where different parts of plants (leaves or flowers) are consumed especially for medical purposes in Turkey by ICP-OES. The validity of the analytical procedure was checked by analyzing INCT-TL-1 CRM certified reference material. The results from the analysis of CRM were all within the 95% reliability limit. The experiment results comply with the values reported in the literature. The wet decomposition method was used to solubilize the metals. The amount of the heavy metal that had passed to the tea via infusion has also been determined. The lowest and highest amounts of the metals found are: Al 268.0±0.6 and 2164.0±0.6 µg/g, Ba 3.0±0.1 and 101.0±0.6 µg/g, Cr 2.0±0.1 and 8.0±0.1 µg/g, Cu 5.0±0.2 and 64.0±0.8 µg/g, Fe 18.0±0.1 and 1471.0±0.3 µg/g, Mn 121.0±0.4 and 657.0±0.7 µg/g, Ni 2.0±0.1 and 17.0±0.3 µg/g, Sr 6.0±0.2 and 82.0±0.2 µg/g, Zn 15.0±0.1 and 103.0±0.4 µg/g. Cd, Pb and Co were not detected in the tea samples studied.